FULL MOUTH REHABILITATION IN GENETIC DISORDER PATIENTS- A RETROSPECTIVE STUDY - Hinaz, Nashwah; V, Ashok (International Journal of Psychosocial Rehabilitation, 2020)
Aim:The aim of the study is to evaluate full mouth rehabilitation done in genetic disorder patients. Materials And Methods: Data was collected after reviewing the patient records and analyzed between June 2019 to March 2020. The collected data is tabulated and software analysis SPSS to obtain results. Results: Total of 233 cases reported for full mouth rehabilitation. 17.6% of the age group 20 to 39 years, 51% of the age group 40 to 59 years and 31.3% of the age group 80 to 90 years. A total of 52.59% cases were treated with FMR and 4.31% of patients with genetic disorders. Conclusion: Within limitations of this study, Most genetic disorder patients with dental anomaly have undergone full mouth rehabilitation. Education and awareness should be given to the genetic disorder patients who have such dental anomalies to improve their self confidence in the society.